La enseñanza del decaimiento radiactivo a partir de aproximaciones analógicas - Pacheco Sáenz, Diego; Avendaño Cubillos, Aníbal (Revista Científica, 2011)
The motivation of this work is to validate the importance of the study of radioactivity in the teaching of physics. The physical phenomena that occur at the atomic level are nottangible and easy to show, but this in no way should detract from our work as teachers. Our job is to route the knowledge for student learning and this is achieved by building models that relate theories and lead us to approximations of complex models. The expression on radioactive decay have similar forms that explain other phenomena, which include: the fall of real water flowing from a tank. This analogy allows us to compare an event of fluid dynamics with decay, which is why our didactic proposal is aimed at explaining the radioactive decay from an assembly building where the filing of a radioactive series, which is made up of water which leads to a series of containers with holes in their bases. Each new vessel where water is deposited is a new radioactive element, distinguished by a striking color characteristic taken when water is poured.